CUSTOMER LOYALTY STRATEGY FOR SEMEN INDAH GRAHAâS DIGITAL ORDERING PLATFORM - Ranthy Ramadhan, Apel
In a condition where the number of players and the capacity of the cement plant are increasing, the competition in the cement industry is getting fierce due to oversupply. However, not all cement players are aware of the opportunity where building material retailers, as the primary channel for bagged cement sales, will undergo ownership transformation within the next five years, shifting to the second generation (Millennials, 36.3% of total retailer owner population), which are also known as digital natives. This second generation will take over the traditional way of doing business that the first generation (Gen X, 46%) has long practiced.